2020
DOI: 10.1002/adfm.202008515
|View full text |Cite|
|
Sign up to set email alerts
|

Recapitulation of In Situ Endochondral Ossification Using an Injectable Hypoxia‐Mimetic Hydrogel

Abstract: Due to the limited ability for perfusion, traditional intramembranous ossification (IMO) often fails to recapitulate the natural regeneration process of most long bones and craniofacial bones. Alternatively, endochondral ossification (ECO) strategy has emerged and has been evidenced to circumvent the drawbacks in the routine application of IMO. Here, an injectable, poly(glycerol sebacate)‐co‐poly (ethylene glycol)/polyacrylic acid (PEGS/PAA) hydrogels are successfully developed to induce a hypoxia‐mimicking en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…MSCs, derived primarily from the bone marrow, are capable of differentiating into different mesenchymal tissues including cartilage, bone, tendon, ligament, muscle, and adipose tissue. , Many studies on engineering MSC microenvironments have focused on controlling MSC differentiation into bone or cartilage for orthopedic tissue engineering applications. Nevertheless, these tissue engineering applications commonly require the expansion of large numbers of MSCs prior to differentiation; , thus, designing an engineered niche for stem cell expansion may promote the transition of MSC-based therapies to the clinic. MSCs are also known for their functions in immunomodulation. Many preclinical and clinical studies have shown that MSCs have anti-inflammatory and immune-privilege potential and suggested a key role of MSCs in regulating T cells and monocytes through either cytokine-dependent or cytokine-independent mechanisms. These applications highlight once again the necessity of developing proper conditions for MSC expansion and behavior regulation.…”
Section: Biomedical Applications Of Dynamic Hydrogelsmentioning
confidence: 99%
“…MSCs, derived primarily from the bone marrow, are capable of differentiating into different mesenchymal tissues including cartilage, bone, tendon, ligament, muscle, and adipose tissue. , Many studies on engineering MSC microenvironments have focused on controlling MSC differentiation into bone or cartilage for orthopedic tissue engineering applications. Nevertheless, these tissue engineering applications commonly require the expansion of large numbers of MSCs prior to differentiation; , thus, designing an engineered niche for stem cell expansion may promote the transition of MSC-based therapies to the clinic. MSCs are also known for their functions in immunomodulation. Many preclinical and clinical studies have shown that MSCs have anti-inflammatory and immune-privilege potential and suggested a key role of MSCs in regulating T cells and monocytes through either cytokine-dependent or cytokine-independent mechanisms. These applications highlight once again the necessity of developing proper conditions for MSC expansion and behavior regulation.…”
Section: Biomedical Applications Of Dynamic Hydrogelsmentioning
confidence: 99%
“…Poly(glycerol sebacate) (PGS) is a polyester synthesized from glycerin-3 and sebacic acid-2 that has received considerable attention in tissue-engineering applications [ 80 ]. PGS was modified by 3D-printing technology with nano-HA [ 32 ], PEG/TCP [ 81 ], PHB [ 82 ], PCL [ 83 , 84 ], poly(vinyl alcohol) (PVA) [ 85 ], and poly(acrylic acid) (PAA) [ 86 ] to obtain potential scaffolds for reconstruction of bone tissue, especially craniofacial bone. Among the characteristics of an ideal polyester for bone regeneration, there is increasing interest in the development of novel materials with antibacterial properties [ 87 ].…”
Section: Orthopedic Applicationsmentioning
confidence: 99%
“…125,126 Therefore, there is an urgent demand for bone adhesives with low biological toxicity, high mechanical strength, strong water-resistant adhesion, high success rate for bone healing, and excellent fixation performance in wet biological environments. [127][128][129] The ideal bone adhesive can promote new bone regeneration and receive special attention as alternative treatments, offering the potential to make bone repair more personal. Using adhesives to replace traditional invasive materials for bone fracture fixation and repair may revolutionize orthopedic surgery.…”
Section: Bone Adhesivementioning
confidence: 99%